Retrospective evaluation of routine in-hospital observation in 433 patients after CT-guided biopsies. (June 2022) - Fischer, Tim; Baz, Yassir El; Wildermuth, Simon; Leschka, Sebastian; Güsewell, Sabine; Putora, Paul Martin; Dietrich, Tobias Johannes
Background: After computed tomography (CT)-guided interventions, routine in-hospital observation is recommended by the Cardiovascular and Interventional Radiological Society of Europe. Purpose: To evaluate the frequency of delayed major complications or hospitalizations after CT-guided biopsies in patients with initially no or minor complications and to assess whether routine in-hospital observation is justified. Material and Methods: This retrospective study included 433 outpatients after CT-guided biopsy of the thoracic (n = 176), abdominal (n = 129), or musculoskeletal (n = 128) region with subsequent in-hospital observation. Complications were graded according to the current Society of Interventional Radiology recommendations and grouped into minor or major. A complication that occurred during in-hospital observation was defined as delayed complication. A delayed major complication was a newly developed major complication or a progression from an initially minor to a major complication. Hospitalization frequencies were evaluated similarly. Occurrence, 95% confidence intervals (CI), and P values for significant differences between the three organ groups were calculated. If delayed major complications were more frequent than 1%, routine in-hospital observation was considered justified. Results: Delayed, major complication frequencies were: thoracic, 8.2% (95% CI 4.6–13.4); abdominal, 0.0% (95% CI 0.0–2.9); and musculoskeletal, 0.0% (95% CI 0.0–2.9) ( P  < 0.001). Delayed hospitalization frequencies were: thoracic, 8.8% (95% CI 5.0–14.2); abdominal, 1.6% (95% CI 0.2–5.6); and musculoskeletal, 0.0% (95% CI 0.0–2.9) ( P  < 0.001). Conclusion: After thoracic interventions, routine observation is considered justified for patient safety whereas routine observation may be omitted after musculoskeletal interventions. In the abdominal group, no delayed complications were observed, but delayed hospitalization occurred. Thus, in-hospital observation could be justified in a safe patient environment, but remains an individual decision.